OC-069 EFECTIVENESS OF PROPHYLACTIC ONLAY MESH FOR PREVENTION OF TROCAR HERNIA: PRELIMINARY RESULTS OF A RANDOMIZED CLINICAL TRIAL. (13th October 2022) - Ciscar, A; Ruiz, P; Saez, E; Vila, M; Gomez, M; Troyano, D; Abadal, M; Pereira, J A; Badia, J M
Abstract: Aim: Trocar site hernia (TSH) incidence is a common complication of laparoscopic surgery. In the literature there is a lack of tools to prevent it. Our aim was to assess the effectiveness and safety of a prophylactic measure to decrease it. Methods: A multicentric randomized clinical trial was performed in high-risk patients (diabetes mellitus and/or age ≥70 years and/or BMI ≥30 Kg/m 2 and/or extended incision for specimen retrieval) who underwent laparoscopic cholecystectomy in an elective or emergency setting. Patients were allocated to prophylactic onlay polypropylene mesh fixation (intervention) or standard trocar closure (control). The main aim was to analyze the efficacy of the intervention, being TSH incidence the primary outcome. Clinical and radiological follow up was atleast 1 year after surgery. Secondary endpoints were technique-related complications. Results: 134 patients were included (70 and 62 to intervention and control arm, respectively). Groups were homogeneous. Mean [SD] age, 64.8 (17.3) years; 80 (60, 6%) women. The cumulative TSH incidence was lower in the intervention group although not reaching significant differences, either when were radiologically (16 [26.7%] vs 17 [37%], p = 0.294) or clinically assessed (9 [17.6%] vs 9 [24.3], p = 0.593). No differences in surgical site infection, hematoma or seroma were detected. Mean follow-up was 736 days (min. 365 – max. 1294). Conclusions: Our preliminary results points out that the overall TSH incidence is extremely high when properly assessed. A polypropylene onlay mesh would not be an effective measure to decrease the TSH incidence. Radiological evaluation would show more accuracy.